Macrophage Activation Syndrome in Juvenile Systemic Lupus Erythematosus A Multinational Multicenter Study of Thirty-Eight Patients - Parodi, Alessandro; Davi, Sergio; Beatriz Pringe, Alejandra; Pistorio, Angela; Ruperto, Nicolino; Magni-Manzoni, Silvia; Miettunen, Paivi; Bader-Meunier, Brigitte; Espada, Graciela; Sterba, Gary; Ozen, Seza; Wright, Dowain; et al. (Wiley-liss, 2009)
Objective. To describe the clinical and laboratory features of macrophage activation syndrome as a complication of juvenile systemic lupus erythematosus (SLE).Methods. Cases of juvenile SLE-associated macrophage activation syndrome were provided by investigators belonging to 3 pediatric rheumatology networks or were found in the literature. Patients who had evidence of macrophage hemophagocytosis on bone marrow aspiration were considered to have definite macrophage activation syndrome, and those who did not have such evidence were considered to have probable macrophage activation syndrome. Clinical and laboratory findings in patients with macrophage activation syndrome were contrasted with those of 2 control groups composed of patients with active juvenile SLE without macrophage activation syndrome. The ability of each feature to discriminate macrophage activation syndrome from active disease was evaluated by calculating sensitivity, specificity, and area under the receiver operating characteristic curve.Results. The study included 38 patients (20 with definite macrophage activation syndrome and 18 with probable macrophage activation syndrome). Patients with definite and probable macrophage activation syndrome were comparable with regard to all clinical and laboratory features of the syndrome, except for a greater frequency of lymphadenopathy, leukopenia, and thrombocytopenia in patients with definite macrophage activation syndrome. Overall, clinical features had better specificity than sensitivity, except for fever, which was highly sensitive but had low specificity. Among laboratory features, the best sensitivity and specificity was achieved using hyperferritinemia, followed by increased levels of lactate dehydrogenase, hypertriglyceridemia, and hypofibrinogenemia. Based on the results of statistical analysis, preliminary diagnostic guidelines for macrophage activation syndrome in juvenile SLE were developed.Conclusion. Our findings indicate that the occurrence of unexplained fever and cytopenia, when associated with hyperferritinemia, in a patient with juvenile SLE should raise the suspicion of macrophage activation syndrome. We propose preliminary guidelines for this syndrome in juvenile SLE to facilitate timely diagnosis and correct classification of patients.